Implementasi Pendidikan Karakter di Sekolah Dasar Melalui Penguatan Pelaksanaan Kurikulum - Sri Judiani (Jurnal Pendidikan dan Kebudayaan, 2010)
Nowadays we should be proud because the more Indonesian students have succeeded in International Science Olympic. The Indonesian student team was even once to be overall champion in the International Conference of Young Scientists with participant from 19 countries held in Bali on April 12th-7th 2010. On the other hand, some other Indonesian students have shown their disrespectful attitude to public, they like to brawl or fight with the student from other school, get drunk, drugs or narcotic addiction, wild races along the crowded traffic. The phenomenon is then to be the reason for government to conduct â€œPiloting Projectâ€ in 125 schools in 16 districts/cities in within 16 provinces since September 2010. The Objectives of conducting the â€œPiloting Projectsâ€ is to implement the values of character to the students so they can turn their attitude to the positive one. The implementation of character education does not need to be the typical subject nor additional standard of competence but this is, however, integrated into the existing subject or through the self-development and school culture as well as local content.Â ABSTRAKSaat ini pelajar Indonesia semakin banyak yang patut dibanggakan, karena telah berhasil menjuarai olimpiade sains di tingkat internasional. Bahkan, pelajar Indonesia menjadi juara umum dalam Konferensi Internasional Ilmuwan Muda se-Dunia yang diikuti ratusan pelajar SMA dari 19 negara di Bali pada 12-17 April 2010. Namun, tidak sedikit pula pelajar yang tidak punya sopan santun, suka tawuran, minum minuman keras, mabok-mabokan, senang narkotika, dan hobi kebut-kebutan mengendarai sepeda motor di jalan raya. Melihat kenyataan ini maka Pemerintah mulai tahun ajaran 2010 telah melakukan piloting penyelenggaraan pendidikan karakter di 125 sekolah yang tersebar di 16 kabupaten/kota dari 16 Propinsi. Implementasi pendidikan karakter di sekolah tidak merupakan mata pelajaran tersendiri, tidak pula merupakan tambahan standar kompetensi (SK) dan kompetensi dasar (KD), tetapi dapat diintegrasikan ke dalam mata pelajaran yang sudah ada, pengembangan diri, dan budaya sekolah, serta muatan lokal.